(untitled) (Journal of Economic Research & Business Administration, 2018)
The authors discussed the main directions of increasing the efficiency of human capital management in agriculture of Kazakhstan. Human capital plays an important role in the economy, its development solves many socio-economic problems, accelerate innovative development in the country. The growth of quantitative and qualitative parameters of human capital development in agriculture in the modern economy, enhancing its competitive advantage possible through effective data management process. Conducted an analysis of employment’ dynamics in agriculture.The main objectives of increasing the efficiency of human capital management in agriculture: smoothing of structural imbalances in the labour market, support of young specialists; improved financial incentives for employees; mitigation of the seasonality of work; conducting qualitative personnel work, etc. The authors present a variant of the system of socio-economic conditions for effective development of human capital in agriculture, where the underlying system is the planning and forecasting of human resource development, and improving development effectiveness, utilization and management of human capital in the agricultural sector. Were made correlation analysis, which revealed that income level significantly affects agricultural productivity, the skill level of employees and average annual wages. The majority of investigated farms belong to the second group, with incomes from 2000 to 3871,5 thousand tenges, which have high enough productivity and shares of workers in higher skill level in comparison with the third group of farms. Therefore, the authors propose to stimulate the workers of the main production to achieve the efficient functioning in agriculture.